2015
DOI: 10.1016/j.rboe.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic treatment for chronic lateral epicondylitis

Abstract: ObjectiveTo report the clinical and functional results from arthroscopic release of the short radial extensor of the carpus (SREC) in patients with chronic lateral epicondylitis that was refractory to conservative treatment.MethodsOver the period from January 2012 to November 2013, 15 patients underwent arthroscopic treatment. The surgical technique used was the one described by Romeo and Cohen, based on anatomical studies on cadavers. The inclusion criteria were that the patients needed to present lateral epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Perhaps this can be prevented by avoiding the decortication of the epicondyle, in view of good results only with the debridement of injured soft tissues. When the discomfort does not improve after exhausting the conservative measures for at least 6 months, arthroscopic treatment is an option for lateral epicondylitis, good results can be obtained with an early return to work without restriction [4]. In conclusion we can say that arthroscopy is becoming a safe option every day for the treatment of recalcitrant lateral epicondylitis, with few complications.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Perhaps this can be prevented by avoiding the decortication of the epicondyle, in view of good results only with the debridement of injured soft tissues. When the discomfort does not improve after exhausting the conservative measures for at least 6 months, arthroscopic treatment is an option for lateral epicondylitis, good results can be obtained with an early return to work without restriction [4]. In conclusion we can say that arthroscopy is becoming a safe option every day for the treatment of recalcitrant lateral epicondylitis, with few complications.…”
Section: Discussionmentioning
confidence: 80%
“…One patient presented discomfort associated with reflex sympathetic dystrophy (Complex regional pain type 2). Bercelo et al [4] reported a patient with associated paresthesia in the lateral forearm area. None of our three patients showed signs of neurological injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Arthroscopic surgical treatment of recalcitrant lateral epicondylitis, 10 cases had found scores more than 90 points ranged from a minimum of 60 points to a maximum of 100 points (mean of 90), which matches the data in the literature in relation to good functional scores. In another study by Bernardo, 18 Arthroscopic management for tennis elbow. The VAS pain score decreased from a preoperative mean of 9.2 to a postoperative mean of 0.64 ,While in or study the VAS pain score improved from a preoperative mean of 8.8 to a postoperative of 0.85 and after follow up six months improved to a mean of 0.6 .…”
Section: Postoperative Rehabilitation and Follow Upmentioning
confidence: 99%
“…Recent literature has focused on exploring outcomes of arthroscopic release and has contributed to the growing support of arthroscopy as a viable method of ECRB release for recalcitrant cases 39-42 . Studies of functional recovery after surgical ECRB release indicated that patients can typically return to play within 3-6 months after surgery 43 .…”
Section: Elbow Injuriesmentioning
confidence: 99%